2008
DOI: 10.1364/oe.16.017654
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence relaxation in the near–field of a mesoscopic metallic particle: distance dependence and role of plasmon modes

Abstract: We analytically and numerically analyze the fluorescence decay rate of a quantum emitter placed in the vicinity of a spherical metallic particle of mesoscopic size (i.e with dimensions comparable to the emission wavelength). We discuss the efficiency of the radiative decay rate and non-radiative coupling to the particle as well as their distance dependence. The electromagnetic coupling mechanisms between the emitter and the particle are investigated by analyzing the role of the plasmon modes and their nature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 22 publications
4
93
0
Order By: Relevance
“…In other words, this resonance condition is exactly equalled to the one of the case of a small distance between a molecule and flat substrate [16]. Indeed, it has been noted in [8,33] that at very small distances between the dipole and sphere surface as compared to the sphere radius, the sphere can be considered as a flat substrate from the point of view of the reflected part of the Green function. In other words, the well-known electrostatic approximation [1,20] may be applied in this case.…”
Section: Resultsmentioning
confidence: 93%
“…In other words, this resonance condition is exactly equalled to the one of the case of a small distance between a molecule and flat substrate [16]. Indeed, it has been noted in [8,33] that at very small distances between the dipole and sphere surface as compared to the sphere radius, the sphere can be considered as a flat substrate from the point of view of the reflected part of the Green function. In other words, the well-known electrostatic approximation [1,20] may be applied in this case.…”
Section: Resultsmentioning
confidence: 93%
“…This problem has an exact analytical solution based on Mie scattering theory [28][29][30]. The presence of the metallic NP near a dipole emitter introduces an additional nonradiative decay channel which depends only on the material property of the metal.…”
Section: Dependence On the Ag Sizementioning
confidence: 99%
“…The most important parameter for the efficient QW-SP coupling is the distance from the metallic NPs to the emitter [10,[30][31]. If the dipole emitter is close to the NPs, the quantum efficiency increases because of the stronger QW-SP coupling and light scattering.…”
Section: Dependence On the Quantum-well Positionmentioning
confidence: 99%
“…Basically SPR is a collective oscillation of free electrons through the whole NP. An important application of SPR is for the enhancement of the spontaneous emission, e.g., the fluorescence of molecule [1][2][3][4][5][6][7][8][9][10][11][12][13] or the photoluminescence of quantum dot [14,15]. Although a metallic nanostructure can indeed induce a strong electric field locally around itself, a few of researches showed that sometimes the overall effect of metallic NP on the fluorescence of a nearby molecule could be the quenching [16] rather than the enhancement [8,9,11].…”
Section: Introductionmentioning
confidence: 99%